A radioimmuno-precipitation assay for antibodies to botulinum A. - Palace, J; Nairne, A; Hyman, N; Doherty, T; Vincent, A (1998)
We quantified antibodies to botulinum A (anti-BTx) by immunoprecipitation of 125I-BTx. We tested seven bioassay-positive sera and 68 coded samples, including 18 from patients who had ceased to respond to BTx treatment. Compared with values from healthy control subjects and 42 neurologic control subjects, all bioassay-positive sera were positive (range, 258 to 2,809 pM) and 49 of 50 patients who continued to respond to BTx were negative (<130 pM). This simple, specific, sensitive, and quantitative assay should prove helpful in the investigation of BTx resistance.